The study of terrorist leadership: where do we go from here?. Issue 3 (18th September 2017) - Hofmann, David C.
Abstract : Purpose: Despite the recognition of the importance of leaders for the formation and ongoing success of social and political movements, the study of leadership in terrorist groups remains underdeveloped. The purpose of this paper, therefore, is to stimulate additional research into terrorist leadership in three main ways: by providing a broad overview of the theoretical perspectives that scholars have used to examine terrorist leadership, by critically reviewing the current state of the academic literature on terrorist leadership, and by presenting various ways in which future research on terrorist leadership can be improved. Design/methodology/approach: This paper takes a conceptual and critical approach to reviewing the scholarly literature on terrorist leadership, and draws upon the author's expertise with the wider multidisciplinary literature on leadership to make methodological and conceptual recommendations to improve related future research. Findings: There is a paucity of empirical and theoretical research devoted to understanding important social and strategic aspects of terrorist leadership, and existing scholarly research is largely conducted in isolation with differing methodological and epistemological starting points. This has hampered efforts to measure, operationalize, and understand key concepts involving leadership in terrorist groups. Practical implications: This paper provides several methodological and conceptual recommendations by which future research on terrorist leadership can be improved from insights taken from the wider scholarly literature on leadership. By virtue of being published in a criminology journal, this paper helps disseminate and expose key concepts in the study of terrorism to related disciplines. Originality/value: This paper provides a general overview of the strengths and weaknesses of the study of terrorist leadership to scholars and students interested in the topic. It provides a foundational discussion of how the current literature on terrorist conceives of and utilizes the concept of leadership. It also provides methodological and conceptual recommendations to improve future research on terrorist leadership.